IMPORTANCE OF TEACHING ENGLISH AS A FOREIGN LANGUAGEIN HIGHER EDUCATION IN UZBEKISTAN - Akramovna, Fazilova Nodira (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
This article describes the great importance and opportunities given to foreign languages in the Republic of Uzbekistan, the purpose of teaching a foreign language and the innovative technologies required for their study. In addition, the reasons and effectiveness of teaching English, especially, in higher education are widely covered.